Chorionic and amniotic membrane-derived stem cells have distinct, and gestational diabetes mellitus independent, proliferative, differentiation, and immunomodulatory capacities - Chen, Liyun; Merkhan, Marwan M.; Forsyth, Nicholas R.; Wu, Pensee (Stem cell research, 2019)
Placental membrane-derived mesenchymal stem cells (MSCs), with the advantages of being non-invasive and having fewer ethical issues, are a promising source for cell therapy. Gestational diabetes (GDM) alters the uterine environment and may affect the therapeutic potential of MSCs derived from placenta. Therefore, we evaluated the biological properties of amniotic (AMSCs) and chorionic membrane MSCs (CMSCs) from human GDM placenta in order to explore their therapeutic potential. In comparison of GDM-/Healthy- CMSCs and AMSCs, the immunophenotypes and typical stellate morphology of MSC were similar in CMSCs irrespective of disease state while the MSC morphology in GDM-AMSCs was less evident. GDM- and Healthy- CMSCs displayed an enhanced proliferation rate and tri-lineage differentiation capacity compared with AMSCs. Notably, GDM-CMSCs had a significantly increased adipogenic ability than Healthy-CMSCs accompanied by increased transcriptional responsiveness of PPARγ and ADIPOQ induction. The secretome effect of Healthy- and GDM- CMSCs/AMSCs by using conditioned media and coculture experiments, suggests that GDM- and Healthy- CMSCs provided an equivalent immunoregulatory effect on suppressing T-cells activation but a reduced effect of GDM-CMSCs on macrophage regulation. However, Healthy- and GDM- CMSCs displayed a superior immunomodulatory capacity in regulation of both T-cells and macrophages than AMSCs. In summary, we highlight the importance of the maternal GDM intrauterine environment during pregnancy and its impact on CMSCs/AMSCs proliferation ability, CMSCs adipogenic potential, and macrophage regulatory capacity. •Chorionic MSCs have a longer morphological aspect and reduced surface area vs. amniotic MSCs.•Chorionic MSCs display superior proliferation and tri-lineage differentiation potential vs. amniotic MSCs.•GDM CMSCs display an enhanced adipogenic capacity in comparison to Healthy CMSCs.•GDM MSCs and Healthy MSCs' secretome demonstrate the ability to supress IL-2 secretion and induce M2 macrophage polarization.